Modelling the Dynamics and Control Efforts of Human Rabies Epidemic - Nur’Ain Zuraida, Ishak (Universiti Malaysia Sarawak (UNIMAS), 2019)
Rabies has been known to occur in Malaysia since 1884. It was only since 1924 that records of human cases have been kept. Most of these cases occurred in Malaysian states bordering Thailand, which is highly endemic of rabies. Sarawak is the first state in Malaysia that recorded 12 rabies death where its outbreak started since July 2017. Mathematical approach can be an important tool in epidemiology study. For understanding disease dynamics, predicting outbreak severity, assessing effectiveness of control interventions, and strive to optimize the development of control measures, epidemiological model is the exact model. In this paper, a theoretical study on the dynamics and control efforts of human rabies epidemic is carried out. A mathematical compartmental susceptible-exposed-infectiousvaccinated (SEIV) model for the dog-human transmission of rabies, taking both domestic and stray dog into consideration is constructed. The control measures include vaccinating susceptible dogs and culling stray dogs. The governing equations are solved numerically using deSolve package in R programming. An interactive web application is built for helping public health practitioners to investigate the dynamics and control effort of human rabies epidemic theoretically.